Preparation and Characterization of Reduced Graphene Oxide /TiO2 Blended Polyphenylene sulfone Antifouling Composite Membrane With Improved Photocatalytic Degradation Performance - Dai, Fengna; Zhang, Shangying; Wang, Qi; Chen, Haiquan; Chen, Chunhai; Qian, Guangtao; Yu, Youhai (Frontiers in Chemistry, 2021)
Nanosized titanium oxide (TiO2)-based photocatalysts have exhibited great potential for the degradation of organic contaminants, while their weak absorption of visible light limits the photocatalytic efficiency. Herein, a novel reduced graphene oxide/TiO2-polyphenylenesulfone (rGO/TiO2-PPSU) hybrid ultrafiltration membrane has been successfully prepared via a non-solvent induced phase-separation method, in which the synergistic coupling between the rGO and TiO2 could endowed the fabricated membranes with visible-light-driven efficient photocatalytically degradation of organic pollutants and outstanding photocatalytic and antifouling properties. Compared with the PPSU membranes prepared with GO and TiO2, respectively, the rGO/TiO2-PPSU membrane demonstrated significant photodegradation towards phenazopyridine hydrochloride (PhP) solution under UV light (improved about 71% and 43%) and visible light (improved about 153% and 103%). The permeability and flux recovery rates of the membrane indicated that the high flux of the rGO/TiO2-PPSU membrane can be greatly restored after fouling, due to the improved self-cleaning properties under visible light static irradiation. With the properties of high performance of photocatalytic degradation and good self-cleaning ability, the rGO/TiO2-PPSU membrane would have great potential in water treatment.